Diversity of Fusarium species on sorghum grain - A. H. RAJASAB*, MOHAMMED SHABBIR. S. and (Indian Phytopathology, 2004)
Grains of three varieties of sorghum, M-35, Bilijola and Chittapur local were collected from kharif and rabi season crops during 2000, 2001 and 2002 to determine the incidence and diversity of Fusarium species colonizing sorghum grain. One thousand eight hundred seventy three Fusarium isolates were recovered from different sorghum grains that belonged to eight species. Fusarium verticillioides was the most prevalent (39%), followed by F. semitectum (36%), F. proliferatum (10.8%) and F. nygamai (10.5%). Other Fusarium spp. viz., F. compactum, F. oxysporum, F. solani and F. scirpi were infrequently recovered. Maximum incidence of Fusarium spp. was observed on grains of M-35 variety grown during rabi season compared to Bilijola and Chittapur local varieties. Incidence of Fusarium spp. was higher in hylar region than in the stylar and middle regions of sorghum grain.